Utilization of brown algae (Sargassum Sp) as dental impression material: Pemanfaatan alga cokelat (Sargassum Sp) sebagai bahan cetak kedokteran gigi - Baharuddin M, Ranggang; Muhammad Ihsan; Wd. Hikmah Noor Shafar Nafiu; Aulia Anindita Ainayyah; Mohammad Resky Asri Putra; Rezky Ayu Pratiwi; Nurul Aulia Azti Azis (Makassar Dental Journal PDGI Makassar, 2022)
ABSTRACT Two-thirds of Indonesia's territory is mostly waters. The United Nations Convention on the Law of the Sea in 1982 stated that the area of ​​Indonesian waters is 5.8 million km2 and there are 27.2% of all flora and fauna species. Algae is one of the most abundant biological resources in Indonesian waters, which is about 8.6%. In Indonesian waters, there are about 28 species of brown algae from six genera including Dyctyota, Padine, Hormophysa, Sargassum, Turbinaria andHydroclathrus. Brown al-gae have a large alginate content in their cell walls, approximately 40% of their dry weight. The alginate contained in brown al-gae canbe used in industrial fields, such as the dental impression material industry. The main active ingredients in the manufac-ture of irreversible hydrocolloid impression materials are sodium alginate, potassium alginate, and triethanolamine alginate. Sodium alginate and potassium alginate can be extracted from brown algae species such as Sargassum sp.